True Multilateralism: Conceptual Development, Core Essences, and China’s Practices - Bo, Chen (Napredak, 2025)
At present, the profound changes unseen in a century are intensifying globally, and global governance encounters a growing array of challenges. The international community needs to advance global governance through true multilateralism. Nevertheless, unilateralism and hegemonism are undermining multilateralism, which faces significant obstacles. China actively advocates and practices true multilateralism, a concept it has proposed, refined, and developed. The core principles of true multilateralism include upholding fairness and justice, maintaining openness and inclusiveness, adhering to the purposes and principles of the UN Charter, promoting extensive consultation, joint contribution, and shared benefits, and keeping pace with the times. China advances true multilateralism through concrete actions, such as nurturing the idea of a community with a shared future for mankind, safeguarding the UN system, enhancing multilateral mechanisms, providing high-quality international public goods, and promoting legal frameworks in global governance.